How aggressive calls of a Neotropical treefrog vary among different levels of social tension?. Issue 4 (4th July 2021) - Brasileiro, Ana C.; Cascon, Paulo; Passos, Daniel C.
Abstract : The treefrog Pithecopus nordestinus emits aggressive calls during agonistic interactions between males, but how these vocalizations vary between contexts with different levels of aggression remains unknown. Herein, we compared the acoustic parameters of aggressive calls emitted during physical disputes and out of fight contexts. The aggressive calls emitted during physical clashes (Fighting Calls) presented a repetition rate, duration and number of pulses significantly higher than those emitted out of fight contexts. Our results expand the knowledge about acoustic repertoire of Phyllomedusidae treefrogs and contribute to the understanding of the effects of social tension on the vocal behavior of anurans.